EGNOS: il GPS Augmenting System per l'Europa - Pititto, Gianluca (GEOmedia, 2010)
EGNOS: Europe's GPS Augmenting System Today, the actual positioning satellite technology allows a great number of civil applications for our life, but many of them are not yet achievable due to the low level of performance of the positioning service actually available. To use GPS for specific applications for which it was not initially designed, industry and reserchers have been designing and implementing technologies to improve its performances. This complementary systems, known as "augmentation systems”, are made up of ground-base (GBAS), space-based (SBAS) or receiver-level infrastructures and technologies. In this second article we continue to explore the GNSS technologies, presenting a summary of the existing SBAS infrastructures, with the focus on EGNOS (European Geostationary Navigation Overlay System).